Open Innovation and CrowdRE for Requirements Change Management in Software Ecosystems - Malcher, Paulo; Viana, Davi; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Software ecosystems (SECO) have introduced complexity in requirements change management due to their open and dynamic nature. In SECO, multiple actors collaborate across organizational boundaries and can form distinct crowds that communicate requirements changes. This work proposes a method to assist professionals in requirements change identification in SECO (SECO-RCI) based on open innovation and crowd-based requirements engineering (CrowdRE). We applied Design Science to build SECO-RCI and evaluated its acceptance via a focus group with experts and its feasibility via a case study in a large real-world scenario. The focus group indicated positive acceptance of SECO-RCI, highlighting its ease of use, usefulness, and intention to use. The case study revealed the absence of a standardized approach for requirements change identification and emphasized the importance of centralized visibility across feedback channels. These findings suggest that SECO-RCI assists in addressing key challenges of requirements change in SECO. Consequently, SECO-RCI can improve software quality in complex and distributed development environments, promoting transparent and collaborative management of evolving requirements.